Hierarchical star formation in nearby galaxies - Rodriguez, Maria Jimena (2020)
Aims. The purpose of this work is to study the properties of the spatial distribution of the young population in three nearby galaxiesin order to better understand the first stages of star formation.Methods. We used ACS/HST photometry and the "path-linkage criterion" in order to obtain a catalog of young stellar groups (YSGs)in the galaxy NGC 2403. We studied the internal distribution of stars in these YSGs using the Q parameter. We extended theseanalyses to the YSGs detected in in NGC 300 and NGC 253 our previous works. We built the young stars? density maps for thesethree galaxies. Through these maps, we were able to identify and study young stellar structures on larger scales.Results. We found 573 YSGs in the galaxy NGC 2403, for which we derived their individual sizes, densities, luminosity function,and other fundamental characteristics. We find that the vast majority of the YSGs in NGC 2403, NGC 300 and NGC 253 present innerclumpings, following the same hierarchical behavior that we observed in the young stellar structures on larger scales in these galaxies.We derived values of the fractal dimension for these structures between ∼ 1.5 and 1.6. These values are very similar to those obtainedin other star forming galaxies and in the interstellar medium, suggesting that the star formation process is regulated by supersonicturbulence.